2019
DOI: 10.1175/jas-d-18-0282.1
|View full text |Cite
|
Sign up to set email alerts
|

Intensification Variability of Tropical Cyclones in Directional Shear Flows: Vortex Tilt–Convection Coupling

Abstract: The coupling of vortex tilt and convection, and their effects on the intensification variability of tropical cyclones (TCs) in directional shear flows, is investigated in this study. The height-dependent vortex tilt controls TC structural differences in clockwise (CW) and counterclockwise (CC) hodographs during their initial stage of development. Moist convection may enhance the coupling between displaced vortices at different levels and thus reduce the vortex tilt amplitude and enhance precession of the overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 28 publications
3
17
0
Order By: Relevance
“…The upward dynamic forcing is likely attributed to the low-level convergence in the downshear convergence zone, and it is difficult to further decompose the dynamical forcing to quantify the relative contribution of the low-level convergence and other mechanisms. The role of dynamic forcing in the convective initiation in the incipient eyewall is consistent with the findings in previous modeling studies of TCs(Zhang et al 2000;Braun 2002;Gu et al 2019). One new finding in this study is that the buoyancy forcing also plays a role in the convective initiation at the inward flank of the CPS (Figs.15c and 15f).Figures 15 and 11 also indicate a striking difference between the two experiments: in CTL a large portion of these parcels have already developed or are going to develop into deep convection in the downwind part of the azimuthally-propagating CPS, as seen in Figs.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…The upward dynamic forcing is likely attributed to the low-level convergence in the downshear convergence zone, and it is difficult to further decompose the dynamical forcing to quantify the relative contribution of the low-level convergence and other mechanisms. The role of dynamic forcing in the convective initiation in the incipient eyewall is consistent with the findings in previous modeling studies of TCs(Zhang et al 2000;Braun 2002;Gu et al 2019). One new finding in this study is that the buoyancy forcing also plays a role in the convective initiation at the inward flank of the CPS (Figs.15c and 15f).Figures 15 and 11 also indicate a striking difference between the two experiments: in CTL a large portion of these parcels have already developed or are going to develop into deep convection in the downwind part of the azimuthally-propagating CPS, as seen in Figs.…”
supporting
confidence: 90%
“…In the presence of VWS, dry TC-like vortices are usually vertically tilted (Jones 1995(Jones , 2004. When coupled with moist processes, the balanced mesoscale lifting associated with the tilted vortex organizes a convective precipitation shield (CPS) in the downtilt side (e.g., Wang and Holland 1996;Corbosiero and Molinari 2002;Reasor et al 2013;Gu et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental shear ows can heavily in uence the variability of the intensi cation rate of tropical cyclones 33 . It is important to understand the mechanisms of and relationships between tropical cyclone intensi cation and shear ows.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the DLS, several studies have examined the impact of assorted characteristics of the sheared background flow profile on TC intensity. Idealized simulations, with 10 m s 21 DLS, have shown that shear height and depth (Finocchio et al 2016) and tropical cyclone-relative environmental helicity (hereafter referred to as TCREH; Nolan 2011; Onderlinde andNolan 2014, 2016;Gu et al 2018Gu et al , 2019 can modulate the intensity evolution and inner-core structure. The deep-sheared layer, upper-level shear, and positive TCREH are more favorable to the upshear precession process and intensification.…”
Section: Introductionmentioning
confidence: 99%